(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
Cities change and grow unpredictably. Recently the transformations of the urban tissue are extensive and important especially in the cities of the emerging countries. Contemporary urban developments scarcely consider what could be learnt from existing urban fabric pursuing generic western-taste solutions ending up into ineffective urban schemes. Since we realize how difficult it is to foresee speed growth, it would be useful to consider a different, more flexible approach. Interpreting urban design as a collective form, a man-made landscape, with landmarks emerging and fabric extending, is what Fumihiko Maki suggests in his writing Investigations in Collective Forms. This was an interesting approach to be verified in 2013, during a one-week Field Studio in Hangzhou at Zhejiang University of Technology Campus. The problem to renovate an area selected from the historic urban tissue in the inner-city – No. 224 and No. 236 of West Lake Road – was investigated through a design approach that combines a traditional courtyard house typology with sequential and flexible schemes.